Enhanced longitudinal compressive strength of CFRP composites with interlaminar CNT film prepreg from hot-melt pre-impregnation. (January 2023) - Zhu, Zaibin; Lu, Kangyi; Ling, Hui; Yu, Yunhua; Li, Gang; Yang, Xiaoping
Abstract: High strength, high modulus and the balance of compressive and tensile strength gradually became the main development goals of advanced CFRP composites. However, the low ratio of compressive and tensile strength of CFRP composites have limited the application as structural materials in aerospace field. In this study, CNT film prepreg (CNT-f-p) was prepared by hot-melt pre-impregnation and used to fabricate the interlayer stiffened and reinforced CFRP composites with enhancement of compressive strength, and the effect of CNT-f-p on longitudinal compressive strength and elastic-plastic failure mechanism of composites were firstly investigated from the experimental results and theoretical model. The tensile strength and modulus of CNT-f-p were enhanced due to sufficient and uniform infiltration of CNT network by resin matrix. The interlaminar shear strength and in-plane shear modulus of CFRP/CNT-f-p composites were improved due to effective CNTs bridging and riveted CNTs between resin and fiber in interlaminar region of composites. The compressive strength of CFRP/CNT-f-p composites was enhanced by 13.2%, showing a consistency with predicted results of Jumahat's combined model, which ascribed to restricted kink-band formation and avoided interface delamination during elastic-plastic compression process of composites from improved transverse support and interfacial adhesion. Consequently, this work presented a potential application in fabrication of CFRP composites with high compressive strength. Graphical abstract: Image 1 Highlights: High-performance CNT film prepreg is prepared by hot-melt pre-impregnation. Insertion of CNT film prepreg effectively improves interlaminar properties and in-plane shear strength of CFRP composite. Interlaminar CNT film prepreg has positive effect on longitudinal compressive strength of CFRP composite. Restricted kink-band formation and avoided interface delamination are achieved in CFRP/CNT-f-p composite.